Improving Students' Comprehension of Narrative Texts Through Educaplay Games - Alvia Aisyah (Universitas Negeri Surabaya, 2026)
This quantitative study used a pre-experimental design to test the improvement in students' understanding of narrative texts in English language learning through the use of Educaplay web-based learning media. Thirty-four eleventh-grade students from a private high school who took English classes were the subjects of this study. In this study, the researcher used multiple-choice tests administered in the form of pre-tests and post-tests as research instruments. To determine whether there was a difference in scores before and after the treatment, the researcher used a paired sample t-test. After that, the researcher measured the strength of the treatment effect using Cohen's d, and the results obtained showed a significant increase and difference in students' understanding of narrative texts after the treatment was given. The results of the analysis showed a significant difference in students' understanding of narrative texts, as indicated by a p-value < 0.001. In addition, a Cohen's d value of 1.6 indicates a strong effect. The findings of this study prove that Educaplay is an effective digital tool for improving students' understanding of narrative texts in English language learning.